Use of Magnesium Silicate as a New Type of Adsorbent for Dispersive Solid-Phase Extraction Cleanup of the Quick, Cheap, Effective, Rugged, and Safe Method for Pesticides During Analysis of Lager Beer by Gas Chromatography-Tandem Mass Spectrometry. (23rd November 2019) - Navickiene, Sandro; Santos, Luis Fabrício Santana; dos Reis Silva, Alexandre
Abstract: Background: Pesticides are applied for pest control during the production of cereal grains used in beer production. Given the risks for consumers, it is important to analyze the pesticide residues. Objective: Quick, easy, cheap, effective, rugged, and safe (QuEChERS)-based methods are very effective, and improvement inthe cleanup step is an important approach. Methods: Primary secondary amine (PSA) andmagnesium silicate were evaluated for dispersive-solid-phase extraction (d-SPE) cleanup step in extracts provided by the QuEChERS method in combination with GC-tandem MS for the determination of acetamiprid, terburfos, alachlor, ametryn, atrazine, azoxystrobin, carbofuran, carbosulfan, cypermethrin, deltamethrin, difenoconazole, esfenvalerate, flutriafol, thiamethoxam, and parathion-methyl in lager beer. Results: The amount of 50 mg of magnesium silicate was suitable for cleaning up beer extract as an alternative d-SPE material to PSA. Themethod was validated using beer fortified with pesticides at three concentration levels (0.002, 0.01, and 0.1 μg/mL). Average recoveries ranged from 70 to 123%, with RSDs between 0.3 and 10.5 %. Matrix effects were observed by comparing the slope of matrix-matched standard calibration with that of solvent. The method provided good linearity at the concentration levels of 0.001–2.5 μg/mL. Detection limits ranged from 0.0001 to 0.0007 μg/mL and quantification limits ranged from 0.001 to 0.006 μg/mL. The method was applied to nine beer brands. Conclusions: Results showed that magnesium silicate is an efficient alternative cleanup material to reduce analysiscosts while maintaining the method reliability and accuracy. Highlights: Magnesium silicate was effective as adsorbent for d-SPE step inthe analysis of pesticides in beer.